La planification de l’action publique à l’échelle du planning - Jean-Marie Pillon; Olivier Quéré (Temporalités)
This article sheds light on the construction and uses of timetables in public administrations. Comparing two compatible examples of fieldwork – a survey in an applied school for middle ranking civil servants and a survey in a one-stop shop for job seekers – the paper shows the extent to which collective work schedules are devices whereby human resources are made to fit material resources over time. Agendas reveal what managers are aiming at, and how major administrative shifts – like new public management-oriented initiatives – tend to modify everyday life in public workplaces. On the other hand, as street level bureaucrats become more and more aware of the importance of quantitative benchmarks in their managers’ annual evaluations, schedules become objects of conflict and bargaining.